The Relevance of Dietary Polyphenols in Cardiovascular Protection - G. Murillo, Ana; L. Fernandez, Maria (Current Pharmaceutical Design, 2017)
The chemical structure of polyphenols consisting of aromatic rings, capable of quenching free radicals, makes them ideal candidates to protect against oxidation. Polyphenols are present in a variety of foods including grapes, berries, dark chocolate, coffee and tea to mention a few. A number of studies have shown that dietary polyphenols exert a protective effect against hypertension, dyslipidemias, inflammation, endothelial function and atherosclerosis, conditions associated with increased risk for cardiovascular disease. Studies indicate that by decreasing cholesterol absorption, polyphenols alter hepatic cholesterol homeostasis resulting in decreases in plasma lipids and reduction in atherogenic lipoproteins thus having a protective effect against atherosclerosis; polyphenols have also been shown to decrease the activity of enzymes involved in the renin-angiotensinaldosterone system and improve blood pressure. Further, they have been recognized to increase nitric oxide production and to improve endothelial function. In this review we will present some of the evidence derived from epidemiological studies, clinical interventions as well as animal and cell studies supporting the cardioprotective effects of dietary polyphenols.
Keywords: atherosclerosis